SINGLE CANDIDATES AGAINST THE EMPTY BOX; ON REGIONAL HEAD ELECTIONS 2020 IN INDONESIA - Syaiful Rohman; Biky Uthbek Mubarok (JWP (Jurnal Wacana Politik), 2022)
Regional Head Elections (Pilkada) on 2020 have a positive effect on the implementation of a constitution and at least democracy for measuring political participation, the elections that were held after reform started from a Regional Head who was elected by the Regional People’s Representative Council (DPRD), then elected directly by the community (one man one vote). The direct election then became a simultaneous election in all parts of Indonesia. Until the latest development, namely the presence of a single candidate. The Single Candidate then implies the Empty Box as a companion because there are no candidates or no eligible candidates. This consequence must be accepted due to the Direct-Simultaneous Election system with the threshold record regulations as full of regional head nominations. This gave birth to various interests of political elites and party elites playing in it so that party elites inevitably intervened to whom the letter of recommendation would be given, or consolidation at the elite political level had agreed on a political dowry which then gave birth to a single candidate. This research uses qualitative methods with comprehensive analysis through data collected from the General Election Commission (KPU) and previous research. This paper examines the main factors that gave birth to a single candidate and the political elite’s role in compiling the party’s recommendation letter. The hypothesis that can be seen from the phenomenon of fighting empty boxes is the political dowry factor and the party cadre system’s ineffectiveness in producing leader candidates.